¿Es posible la justicia urbana en Chile? Análisis a la nueva institucionalidad en materia de mitigaciones y aportes al espacio público - Quinteros Flores, Christian (Corporación Universitaria del Caribe, CECAR., 2018)
ABSTRACT Governance, as a new comprehensive approach to territorial dynamics, requires identifying asymmetries of information and power that exist among its actors. In Chile, territorial conflicts derive from an invasive neoliberalism of the soil, added to planning processes without the binding participation of citizens. This work reviews Law No. 20,958, identifying the actors involved in it, its link with processes of citizen participation that seek to assess local territories and their assets. It is concluded that the determining criterion of social inclusion/exclusion in the construction of a city is economic profitability, subordinating the dimensions of social sustainability.